Community-acquired sepsis in the medical intensive care unit – an experience from a lower-middle-income country - Jibril, Huzefa; Ali, Syed Ahsan; Awan, Safia; Khanum, Iffat (Journal of the Pakistan Medical Association, 2024)
Objective: To determine microbiological pathogens and in-hospital mortality in patients admitted with community-acquired sepsis to the intensive care unit in a tertiary-care setting in a low- and middle-income country. Methods: The retrospective, observational study was conducted at the medical intensive care unit of a large tertiary care hospital in Karachi, and comprised data from January 1 to December 31, 2019, and comprised data of patients with community-acquired sepsis who were assessed using the Sepsis-3 criteria. Data was compared between survivors and non-survivors, and independent factors associated with escalation to a higher level of care were identified. Data was analysed using SPSS 23. Results: Of the 135 patients with mean age 49.8±18.0 years, 91(67.4%) were males and 44(32.6%) were females. The most common primary site of infection was the respiratory tract 63(46.7%). In-hospital mortality was noted in 52(38.5%) cases, while there were 83(61.5%) survivors. Serum levels of lactate and bicarbonate as well as urine output, fungal pathogens, septic shock and sequential organ failure were significantly associated with mortality (p<0.05). Conclusions: Clinical and microbiological spectrum of community-acquired sepsis in a low- and middle-income country was found to be different from other regions of the world. Clinicians should keep these differences in mind while managing these critically ill patients. Key Words: Sepsis, Septic shock, Critical care, Drug resistance, Fungi.